Music, Performance, Meaning: Selected Essays - Cook, Nicholas (Hampshire Ashgate, 2007)
This selection of sixteen of Nicholas Cook's essays covers the period from 1987 to 2004 and brings out the development of the author's ideas over these years. In particular the two keywords of the title - Meaning and Performance - represent critical directions that expand to the point that, by the end of the book, they become coextensive: music is seen as social action and meaning as created by that action. Within this overall direction, a wide variety of topics is explored, ranging from Beethoven to Schenker, from Chinese qin music to jazz and rock, from perceptual psychology to sketch studies and analysis of record sleeves. A substantial introduction draws out the links (and differences) between the essays, sometimes critiquing them and always setting them into the developing context of the author's work as a whole.